Alterações no contato social induzidas pela dor reduzem respostas nociceptivas sem modificar comportamento tipo-ansioso - Gonçalves, Amélia Santana Barbosa (2016)
The pain affective- motivational component refers to the effects of the pain experience on emotions and behavior. Studies shown that social contact induces changes in nociceptive responses, as well as in emotional responses including anxiety in individuals with pain. Our objective was to evaluate how pain affects the social contact and how this contact interferes in nociception and behaviour anxious-like of rats with inflammatory pain and its contactantes. Wistar rats were used (n=75), with 2 to 3 months old. For that they were conducted three experiments. The first experiment evaluated the resident rats behavior during contact with control (CTRL) or rats with inflammatory pain (FORM), n =8 animals for group. Therefore, we measured the latency for the first contact and the contact during 20 min. Residents had a lower latency of the first contact (p=0,013) and longer duration of contact (p=0,0004) with animals FORM group. These responses were higher in the intervals of 0 -5 (p< 0,01) and 15 - 20 min (p< 0,001). Experiment II evaluated the effect of social contact in painful behavior of rats in formalin test. The animals were divided into 02 groups (n= 8/group): Formalin isolated (FI) receiving formalin and were isolated and Formalin contact (FC) receiving formalin and had contact with cohabitants animals. After 20 min of contact or isolation, the animals were placed in the observation box and nociceptive responses were evaluated by 40 min. Animals FC group showed lower number of shaken paw in the first 5 min test (p=0,0019). In Experiment III were evaluated the anxiety- like responses with help of perforated plate using as parameter the total distance traveled, duration and number of dives on the board; and open field, the parameters time spent in the central area of the field and total distance traveled as locomotor response. Thus, the rats were divided into 5 groups (n= 8/group): Formalin-isolated (FORM-ISO) animals were injected with formalin and were isolated by 20 min; Formalin-contact (FORM-CON): animals were injected with formalin and returned to the social contact for 20 minutes; Control-isolated (ISOL): the animals were isolated and after 20 minutes; Resident (RESID): the animals which had contact with the FORM-CON group were tested and; Control (CTRL): the animals were submitted directly to the test. Residents animals had higher total distance (p = 0,036) in the test of perforated plate. The number of dives (p = 0,158) and dive time (p = 0,056) were not changed. In the open field was no significant difference in the total distance (p = 0,043), but no difference in time spent in the central zone (p = 0,253) between the groups. The results suggest that rats identify inflammatory pain conditions in other rats and adopt active behavior directed to the animal in pain. Moreover, the social contact between animals of the same colony reduces inflammatory pain, but did not change the behavior anxious-like of rats with inflammatory pain and cohabitants.